Science Means Never Having to Say You're Sorry? Apologies for Scientific Misconduct. Issue 5 (October 2019) - Hesselmann, Felicitas; Reinhart, Martin
Retractions of journal articles exclude fraudulent or erroneous research from legitimate science and perform boundary work. Analyzing retractions from different disciplines and focusing on their apologetic aspects, we find that these apologies shift between openly addressing emotional, normative, and social themes and concealing them in a more scientific style of communication. Their boundary work remains highly ambivalent: They alternate between scientific and nonscientific forms of speaking, portray unstable patterns of control and coercion, and avoid drawing a boundary between legitimate and nonlegitimate science. In line with the hypothetical nature of scientific knowledge, retractions thus leave boundary making to the future.